Randomized clinical trial comparing inguinal hernia repair with Lichtenstein technique using non-absorbable or partially absorbable mesh. Preliminary report - Konrad Pielaciński; Andrzej B. Szczepanik; Andrzej Misiak; Tadeusz Wróblewski (Videosurgery and Other Miniinvasive Techniques)
Introduction: The Lichtenstein technique is currently considered the “gold standard” of open, anterior inguinal herniarepair. It is not free, however, of adverse effects, which may be caused by the implemented synthetic material. Aim: Determination the influence of the mesh employed on treatment results including immediate complications,return to everyday activities, chronic pain occurrence and hernia recurrence. Material and methods: Tension-free hernia repair using the Lichtenstein technique was performed in all the 59patients randomized to trial groups. Group P with heavyweight polypropylene mesh contained 34 patients; group Vwith lightweight, partially absorbable mesh (polypropylene/polyglactin 910) consisted of 25 people. Controlled, scheduledfollow-up appointments took place after the 7th day and the 3rd and 6th month. Patients were clinically assessedand pain intensity was determined on an analogue-visual scale.Results: No statistically significant influence of the type of mesh on the risk of early complications, severe pain intensity,the length of hospital stay, time of recovery, or patients’ satisfaction with treatment was observed. After 6 monthsalso no statistically significant differences were observed between groups with regard to recurrence rate (P 3.4% vs.V 4.0%), chronic pain (P 5.9% vs. V 4.0%) and ailments such as “foreign body presence” (V vs. P, OR = 0.30, 95% CI0.077-1.219, p = 0.093) incidence, although their probability was 70% lower for V mesh. Conclusions: The preliminary results confirm the effectiveness of the Lichtenstein technique for hernia repair withboth types of meshes. It appears that use of a partially absorbable mesh is connected with